Okrepljena ustavna demokracija - Nahtigal, Matjaž (Teorija in praksa, 2013)
The key characteristic of dealing with the financial, economic and social crisis since 2008 is that efforts are being made to solve the crisis on global, European and national levels within the existing limited set of institutions of a representative democracy, market economy and free civil society. A discussion of the alternative institutional possibilities which would comprehensively restructure the constitutional democracy, market economy and free civil society towards a more inclusive, more diverse and more experimental society is not yet on the table. There are regions as exceptions in the first and third world which are recognised as the most advanced regions not only according to the level of their competitiveness, but also according to their social cohesiveness and economic and educational opportunities, as well as their innovation levels. The theoretical basis for the discussion in the context of modern institutional theories is as follows: classical constitutionalism, political parties founded in the nineteenth century and mass Fordist production developed according to the economic principles of the early twentieth century cannot remain an institutional basis for the organisation and functioning of modern democratic societies in the twenty-first century. In order to facilitate more creative, imaginative dialogue at the national level and to strengthen the national development project within the EU context we need a truly independent, autonomous and well-organised civil society. It has to become a partner of political parties. Political parties should be able to develop and excel on the basis of rich and diverse programmatic alternatives. Instead of having a superficial consensus, we should foster and strengthen the discourse on the alternative development pathways and be able to create broad social alliances in striving for such pathways. The past two years were wasted in the national and European constitutional and development context, which is why it will be difficult to redeem this lost period of time.
Keywords: Civil society; Civilna družba; Constitutional system; Democracy; Demokracija; Market economy; Pluralism; Pluralizem; Tržno gospodarstvo; ustavna demokracija; Ustavni sistem